2013
DOI: 10.1186/2251-6581-12-53
|View full text |Cite
|
Sign up to set email alerts
|

Associations of eating a late-evening meal before bedtime with low serum amylase and unhealthy conditions

Abstract: Little is known about the associations of eating a late-evening meal (ELM), a putative unhealthy eating behavior, with low serum amylase, other eating behaviors, and cardiometabolic risk factors. Therefore, we investigated whether ELM before bedtime was associated with low serum amylase or other clinical factors in 2,426 asymptomatic adults aged 20–80 years. Multivariate logistic regression analysis showed that ELM was significantly associated with low serum amylase (<60 IU/l), overweight, smoking, daily alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…After age restriction and exclusion of subjects with incomplete data, 61,364 apparently healthy subjects (36,416 men and 24,948 women), aged 30–70 years, were enrolled. In our previous studies, where the age of subjects ranged from 20 to 75 or 80 years old, the prevalence of hyperglycemia was very low in the younger age group and the prevalence of BS was very low in the older age group [ 6 , 9 ]. Accordingly, in this study, we restricted subjects to those aged 30–70 years.…”
Section: Methodsmentioning
confidence: 99%
“…After age restriction and exclusion of subjects with incomplete data, 61,364 apparently healthy subjects (36,416 men and 24,948 women), aged 30–70 years, were enrolled. In our previous studies, where the age of subjects ranged from 20 to 75 or 80 years old, the prevalence of hyperglycemia was very low in the younger age group and the prevalence of BS was very low in the older age group [ 6 , 9 ]. Accordingly, in this study, we restricted subjects to those aged 30–70 years.…”
Section: Methodsmentioning
confidence: 99%
“…An epidemiology study showed that the habitual intake of late-evening meals was associated with a higher BMI and metabolic risk factors such as high triglycerides and lower high-density lipoprotein cholesterol [23]. A potential explanation for this is the reduced metabolic rate and fuel utilization that occur during sleep [24].…”
Section: Discussionmentioning
confidence: 99%
“…2004;De Ridder, Van den Bos 2006). Najbardziej niekorzystne jest przejadanie się mające miejsce w późnych godzinach, gdyż -jak wskazują wyniki badań -dla powstawania i utrzymywania się nadmiernej masy ciała najbardziej niekorzystny wpływ ma jedzenie w godzinach wieczornych oraz nocnych (Oshida, Kutsuma, Nakajima 2013).…”
Section: Konsekwencje Emocjonalnalnego I Nawykowego Spożywania Nadmieunclassified